'A Tribute to my Brother': Women's Literature and its Post-war Ghosts. (February 2015) - Kennedy, Kate
<x content-type="archive" xml:space="preserve">Abstract</x> This paper analyses the ways in which a selection of influential, middle-class women mourned their brothers' deaths through their writing. Some, inspired by the ghost of their lost brother, self-consciously set out to create and mould the written account of women's suffering in war; others were solely interested in the creative and regenerative effect of the dead brother's presence in their own work, sublimating their own guilt at survival into an impulse to write. Vera Brittain, Katherine Mansfield, Rose Macaulay, and Cicely Hamilton contributed in fiction and autobiography to what we might describe as a specifically female memory of the war, focussed through their depictions of their brothers' deaths. Their writing, particularly in Brittain's case, has played a considerable part in the formation of the sense of the 'lost generation' of the 1920s, which in turn has shaped later perceptions of the war. However, a detailed examination reveals that when these women's writings are read alongside each other, a more troubling and complex picture emerges—we find bizarre manifestations of guilt and grief, and a sense of a mourning that is forbidden and incomplete, revealing itself through hallucination, haunting, and possession. Their narratives speak of the very particular complexity of survival for women, who, in the post-war years, must somehow reconcile their mourning with their own continuing creativity and achievements in the space left by their lost brothers and lovers.